(untitled) (GAIMS Journal of Medical Sciences, 2024)
The District Residency Program (DRP) was one of the novel changes introduced by the National Medical Council (NMC) advocating a community centric objective for the post-graduate medical students. A survey was conducted to study the strengths, weaknesses, opportunities & threats to the program. The residents chiefly complained of the logistics, accommodation & the duration of the program. Despite the early implementation issues amongst other challenges, the program might serve as an important learning module & pave the way forward for improving the health services in the developing countries like India where more than 60% of the population has a limited access to the specialized health care facilities.